2015
DOI: 10.1155/2015/747420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chitosan Concentration on the Protein Release Behaviour of Electrospun Poly(ε‐caprolactone)/Chitosan Nanofibers

Abstract: Poly( -caprolactone)/chitosan (PCL/chitosan) blend nanofibers with different ratios of chitosan were electrospun from a formic acid/acetic acid (FA/AA) solvent system. Bovine serum albumin (BSA) was used as a model protein to incorporate biochemical cues into the nanofibrous scaffolds. The morphological characteristics of PCL/chitosan and PCL/chitosan/BSA Nanofibers were investigated by scanning electron microscopy (SEM). Fourier transform infrared spectroscopy (FTIR) was used to detect the presence of polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…In addition, compared to PCL/chitosan nanofibers, PCL/chitosan/BSA nanofibers showed higher fiber diameter and larger pore size. Results showed that the chitosan ratio affected significantly in the protein release profile from the PCL/chitosan/BSA blend [ 111 ].…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…In addition, compared to PCL/chitosan nanofibers, PCL/chitosan/BSA nanofibers showed higher fiber diameter and larger pore size. Results showed that the chitosan ratio affected significantly in the protein release profile from the PCL/chitosan/BSA blend [ 111 ].…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…The spectrum of the Chitosan-g-PVA containing BSA in Figure 2 shows both peaks for BSA as well as the characteristic peaks for Chitosan-g-PVA without BSA, which confirmed the presence of BSA in the blends (Roozbahani et al 2014). …”
Section: Ftir Spectra Of Filmmentioning
confidence: 56%
“…this stagnation could be an evidence for entrapment of the ICG in the PCL fibers, with the initial burst release due to ICG that was not entrapped but loosely attached to the surface of the fibers. A burst release was observed for other molecules entrapped in ICG fibers, such as BSA . The absorbance of the extracts from patches exposed to daylight showed a significantly lower ICG concentration than the samples stored in the dark.…”
Section: Discussionmentioning
confidence: 94%